Hodnocení finanční situace podniku a návrhy na její zlepšení - Bujáková, Veronika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Předmětem bakalářské práce „ Hodnocení finanční situace podniku a návrhy na její zlepšení“ je analýza současného stavu konkrétní společnosti a návrh na zlepšení její finanční situace. V první části své práce definuji cíle a použité metody vedoucí k zlepšení finanční situace firmy, dále pak představuji společnost DOBET, s. r. o., a zakončena je analýzou současného stavu firmy. Další část se zaměřuje na analýzu daného problému a návrh postupu řešení.

The aim of the Bachelor thesis "Financial Situation assessment of the company and suggestions for its improvement" is to analyze current state of a particular company and submit a proposal for improvement of its financial situation. In the first part of the Bachelor thesis defines the aims and the methods, which can be used to improve the financial situation of the company. Further is presented DOBET, s .r .o. company and analysis of its current state. The second part of the Bachelor thesis is based on analysis of the problem and a proposal to its solution.
Evaluation of the Financial Situation of a Company and Proposals for its Improvement
Keywords: Finanční analýza; finanční zdraví; rentabilita; likvidita; rozvaha; výkaz zisků a ztrát; metody finanční analýzy.; Financial analysis; financial health; profitability; liquidity; balance sheet; profit and loss statement; methods of financial analysis.